2009
DOI: 10.1055/s-0029-1243221
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Performance and Nocturnal HRV Indices

Abstract: The effects of endurance training on endurance performance characteristics and cardiac autonomic modulation during night sleep were investigated. Twenty-four sedentary subjects trained over four weeks two hours per week at an average running intensity of 76+/-4% of their heart rate reserve. The R to R ECG-intervals were recorded and heart rate variability indices including high frequency power (HFP) were calculated for the nights following the training days every week. The subjects were divided into responders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…Similar results to Nummela et al (2010) were found by Buchheit et al (2010) who studied the relationship between endurance performance and HRV by investigating the effects of an 8-week training period to HR-derived indices. They found increased resting vagal-related indices in those subjects who decreased their running time in a 10 km test run and were qualified as "responders" to the training program.…”
Section: Hrv and Endurance Trainingsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results to Nummela et al (2010) were found by Buchheit et al (2010) who studied the relationship between endurance performance and HRV by investigating the effects of an 8-week training period to HR-derived indices. They found increased resting vagal-related indices in those subjects who decreased their running time in a 10 km test run and were qualified as "responders" to the training program.…”
Section: Hrv and Endurance Trainingsupporting
confidence: 78%
“…Usually an overreaching, hard training period is found to decrease nocturnal HRV (Hynynen et al 2007;Pichot et al 2000). Also a link between endurance performance and nocturnal HRV has been found in the study of Nummela et al (2010). The effects of a four-week endurance training period on post-exercise nocturnal HRV and on endurance performance were investigated and a link was found between the improved maximal running speed and increased nocturnal HRV when the subjects were divided into responders and non-responders according to the improvements in maximal treadmill test .…”
Section: Hrv and Endurance Trainingmentioning
confidence: 98%
“…Other authors have reported similar results for endurance sports (Buchheit et al, 2010;Garet et al, 2004). Nummela et al (2010) observed that changes in maximum velocity reached on a treadmill by sedentary individuals after a period of training were consistent with changes in parasympathetic indices. Our study suggests that monitoring vagal activity-related variables could be useful for predicting performance in young athletes throughout the different stages of their development.…”
Section: Discussionsupporting
confidence: 72%
“…Based on these results, good aerobic fitness did not associate with HRV, although increased RMSSD and SDNN were measures reflecting enhanced parasympathetic functioning of ANS. Although this study has not looked at intervention effects of an exercise training program, previous literature shows that exercise training improves HRV and autonomic control of the heart [22,23]. Improved autonomic control of the heart, in turn, enhances recovery processes.…”
Section: Recovery State After the Work Shiftmentioning
confidence: 96%